Biosynthetic and natural nanocarbon production - Md. Abdul Majed, Patwary; Mohammad Atiqur, Rahman; Syed Ragibul, Haque; Bijoy Chandra, Ghos; Md Rezaur, Rahman; Mohammed Mahbubul, Matin; Muhammad Khusairy, Bakri (Elsevier Ltd., 2024)
Carbon, with its various allotropes, is one of the most common elements in the universe. Nanocarbon is an example of an allotrope with a well-defined structure and a particle size on the nanometer scale (Vivekchand et al., 2004). The utilization of various carbon nanomaterials (CNMs) has gained significant traction in recent years, with extensive global research efforts dedicated to exploring their exceptional properties. It is crucial to acknowledge the remarkable technological advancements that can be achieved through the utilization of bio-based carbons, as their potential should not be underestimated (Dalvand et al., 2016; Murthy et al., 2021; Dutta et al., 2022). Exclusively, the vast majority of porous carbons are regarded as cost-effective and possess environmental prominence potential.